Role of chemokines in metastatic niche: new insights along with a diagnostic and prognostic approach. Issue 5 (20th April 2018) - Rezaeeyan, Hadi; Shirzad, Reza; McKee, Trevor D.; Saki, Najmaldin
Abstract : Chemokines are cytokines that are involved in the movement of leukocytes and the occurrence of immune responses. It has recently been noted that these cytokines play a role in the movement of cancer cells to different parts of the body and create a suitable environment [i.e. (pre) metastatic niche] for their growth and proliferation. We studied the role of chemokines in the metastasis of cancer cells, as well as their involvement in the proliferation and growth of these cells. Relevant literature was identified by a PubMed search (2005–2017) of English language papers using the terms 'chemokine, ' 'metastasis niche, ' and 'organotropism.' Based on the nature of cancer cells, the expression of chemokine receptors on these cells leads to metastasis to various organs, which ultimately causes changes in different signaling pathways. Finally, the targeting of chemokines on cancer cells could prevent the metastasis of cancer cells toward different organs.